Systematic analysis of the pharmacology of standardized extracts of human placenta - T. E. Bogacheva; I. Yu. Torshin; O. A. Gromova (Фармакокинетика и Фармакодинамика)
Currently, the study of promising “biogenic stimulants” that exhibit pathogenetic effects in relation to various diseases continues. The first results of studies of peptide “biogenic stimulants” based on human placenta extracts (HPE) were obtained by Prof. Filatov VP in the thirties of the 20th century. Currently, through modern methods of postgenomic pharmacology (including high-precision mass spectrometry, enzyme-linked immunosorbent assay and sequencing), it becomes possible to obtain new data on the structure and functions of peptide extracts, which indicates the molecular pharmacological mechanisms of their action. Analysis of peptide fractions of individual standardized ENPs and the results of clinical studies of these ENPs indicate a wide range of clinical applications of ENPs: (1) liver diseases; (2) viral diseases — COVID-19, etc.; (3) diseases accompanied by iron overload and hyperferritinemia; (4) chronic fatigue syndrome; (5) skin diseases; (6) joint pathologies; (7) acceleration of wound healing; (8) diseases associated with the female reproductive system.